(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
This article provides a comprehensive analysis of the linguocultural aspects of the concept of education. The phenomenon of education is analyzed as a complex phenomenon in the harmony of language, culture, thinking, and social factors. A linguoculturological model of the concept of education has also been developed, and its main components (linguistic, cultural, cognitive, and social) are explained. The results of the research play an important role in the development of the intercultural approach in the modern education system.